The Essay Film: Exploring Genre, Form, and Perception in Indonesian Cinema - Achnas, Nan (IMAJI, 2025)
The essay film has a long and diverse history with a literary heritage that of the essay form. The term ‘essay’ often signifies a range of different categories of writing – from the literary writings to the academic essay. The essay form is both flexible and wide-ranging making it challenging to define what constitutes the form. Essays are continuously going through the process of definition. This re-ordering of the internal power of a medium is what Gilles Deleuze calls systems of perception that in turn establishes hierarchy and coherence in the form that relates to the intention of the creators of the text, the medium, and to the audience. Making sense of the structures of being is always also a matter of thinking about it. In the context of the essayistic form -- they are always something more, and something essentially different than mere reflections. An exploration of the essay form and film will open possibilities of the sub-genre in Indonesian cinema.